2010
DOI: 10.1186/ar3091
|View full text |Cite
|
Sign up to set email alerts
|

New developments in osteoarthritis. Sex differences in magnetic resonance imaging-based biomarkers and in those of joint metabolism

Abstract: Sex differences in the prevalence, incidence, and severity of osteoarthritis (OA) have long been known. Some differences in the evaluation of this issue across studies may be related to differences in study design, sampling, study size, study populations, targeted joint sites, and definitions of OA. This report highlights recent studies of sex differences in individual joint components imaged by magnetic resonance imaging and in systemic biomarkers of joint metabolism. Particularly important are those studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 69 publications
2
39
0
2
Order By: Relevance
“…These sex differences also were found prior to the onset of radiographic knee OA (TFOA KL grade <2) and were present regardless of adjustment for covariates in knees without PF or TFOA. Indeed, Maleki-Fischbach and Jordan 26 suggested that more studies need to specifically examine sex differences in various assessments of OA, and whether risk factors for OA act similarly in both men and women, rather than simply controlling for sex.…”
Section: Discussionmentioning
confidence: 99%
“…These sex differences also were found prior to the onset of radiographic knee OA (TFOA KL grade <2) and were present regardless of adjustment for covariates in knees without PF or TFOA. Indeed, Maleki-Fischbach and Jordan 26 suggested that more studies need to specifically examine sex differences in various assessments of OA, and whether risk factors for OA act similarly in both men and women, rather than simply controlling for sex.…”
Section: Discussionmentioning
confidence: 99%
“…30 A review of sex differences in MRI features of OA and biomarkers of joint metabolism noted variable findings. 31 Women may have thinner and more reduced volume of knee cartilage than men (even after taking into account differences in height, weight, and bone size), whether women have a more accelerated rate of cartilage volume loss than men is not clear.…”
Section: Risk Factors For Radiographic Oamentioning
confidence: 99%
“…A gender dimorphism exists for the impact of OA on pain and quality of life such that women report higher levels of pain and greater reductions in quality of life than men 14,15 . A review of magnetic resonance imaging (MRI) comparisons of men and women highlights variability in findings but concludes that women appear to have lower knee cartilage volume than men 16 . Despite similar KL grades, as compared to men, women exhibit higher levels of the bone resorption biomarker, serum C-terminal telopeptide of collage type I (CTX-I), and the cartilage degradation biomarker, urine C-terminal telopeptide of collage type II (CTX-II) 17 .…”
mentioning
confidence: 99%
“…Despite similar KL grades, as compared to men, women exhibit higher levels of the bone resorption biomarker, serum C-terminal telopeptide of collage type I (CTX-I), and the cartilage degradation biomarker, urine C-terminal telopeptide of collage type II (CTX-II) 17 . In contrast, men exhibit higher levels of serum hyaluronan (HA), an indicator of synovial inflammation suggesting gender-specific pathogenic mechanisms 16 . Gender differences in OA have been attributed to differences in sex hormones, as lower levels of estradiol and its catabolic metabolite, urinary 2-hydroxyestrone are associated with the development of knee OA 18 .…”
mentioning
confidence: 99%